1979
DOI: 10.1159/000458640
|View full text |Cite
|
Sign up to set email alerts
|

Lymphatic Transport of Cellular Enzymes from Muscle into the Intravascular Compartment

Abstract: In an experimental study, employing anaesthetized dogs, it was investigated whether cellular enzymes from peripheral skeletal muscle get into the circulating blood by diffusion across capillary membranes or by lymphatic transport. In the experimental group 1, the animals were anaesthetized only. The plasma activities of the four enzymes measured — lactate dehydrogenase, aspartate aminotransferase, alanine aminotransferase, creatine kinase did not show any mentionable change during a time period of 6 h. In grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0
1

Year Published

1982
1982
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 16 publications
1
31
0
1
Order By: Relevance
“…It was further shown that the plasma enzyme response to spontaneous running exercise in conscious dogs is quantitatively similar to the plasma Tab, l. Enzyme activities in Iymph and plasma (U/l; x ± SEM) and lymph-plasma activity ratio (x ± SEM) in order of dimishing lymph-plasma activity ratio. Probabilities of significance between the muscles: * 2p < 0.05 *** 2p < 0.001 enzyme response evoked by passive movement of the hind limb in anaesthetised dogs (10,33,34,35,36).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It was further shown that the plasma enzyme response to spontaneous running exercise in conscious dogs is quantitatively similar to the plasma Tab, l. Enzyme activities in Iymph and plasma (U/l; x ± SEM) and lymph-plasma activity ratio (x ± SEM) in order of dimishing lymph-plasma activity ratio. Probabilities of significance between the muscles: * 2p < 0.05 *** 2p < 0.001 enzyme response evoked by passive movement of the hind limb in anaesthetised dogs (10,33,34,35,36).…”
Section: Discussionmentioning
confidence: 99%
“…During periöds of physical activity or passive motiöri these activities reach the blood via ductus thoracicus in considerable amount. Recent investigations on changes in the flow of duptus thoracicus Iymph, evoked by passive motion pf the hind limb in äriaesthetised dogs, have shown that these changes in fact can traced back nearly exclusively to Iymph propulsion from the passively moved muscle by action of the tissue pump (10,15). These observations then simply point to the importance of alterations of Iymph flow from muscle for the adjustment of the level pf cellular enzymes of musculär prigin in plasma.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The data are expressed äs the mean and include quality control measurements from 1. c. (14,15,28), in which catalytic activities were determined in lymph, tissue and erythrocytes. Daily quality control for the other enzymes was established with cornmercial control sera of varying batch number.…”
Section: Manmentioning
confidence: 99%